Seasonal variation of the C-2-C-9 hydrocarbons concentrations and compositions emitted from motor vehicles in a Seoul tunnel - Na, K; Kim, YP; Moon, KC (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
The concentrations and compositions of C-2-C-9 hydrocarbons (HQ were measured in a tunnel at Seoul, Korea in winter, spring and Summer, 2000. The average concentrations of ethylene, n-butane and acetylene were the highest species. Though the absolute concentrations of HC ill the tunnel air varied significantly, the compositions of individual species were relatively constant over each season. The ratio of exhaust composition to fuel composition for benzene was > 1, indicating that it is more abundant in the exhaust than that in the fuel. Consequently, to reduce benzene in vehicle emissions, it is necessary to control benzene-producing HC as well as benzene content in vehicle fuel. The most pronounced differences in the tunnel air among the three seasons were higher mass percentage for propane in winter and higher mass percentages of n-/i-butanes it) summer. The amounts of butanes to the total HC in the tunnel air showed a positive relationship (R-2 = 0.71) with the compositions of the butane-fueled vehicles to the total vehicles passing through the tunnel. It showed that butane vehicles are a major contributor to the high concentration of butanes in the tunnel air. Photochemical potential of C-2-C-9 HC measured in summer was evaluated by using the maximum incremental reactivity. For individual compounds, the contribution made by ethylene to the total specific reactivity was the highest, followed by propylene, 1,2,4-trimethylbenzene, toluene and ni-/p-xylene. For five hydrocarbon classes, the contribution of alkenes to the total HC reactivity was the highest. It showed that alkenes were the most important contributor of photochemical ozone formation in the vehicle emissions. The most prominent differences between this study and other studies were higher mass percentages of n-/i-butanes and propane. The reason for this was the wide use of butane-fueled vehicles. Consequently, it was found out that the pattern of fuel usage is an important factor affecting the HC compositions in the vehicle emissions. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: NONMETHANE ORGANIC-COMPOUNDS; TAILPIPE EMISSIONS; EXHAUST; REACTIVITY; PROFILES; AREA